2022
DOI: 10.3390/children9030350
|View full text |Cite
|
Sign up to set email alerts
|

Mediators between Positive and Negative Parenting and Child Depressive and Anxious Symptoms: Findings from a Diverse, At-Risk Sample

Abstract: Background: Although children’s depressive and anxious symptoms have been broadly construed as internalizing problems, the current study sought to identify factors that may differentially contribute to these two mental health problems in a high-risk sample. Prior research has not adequately tested both depressive versus anxious symptoms simultaneously, nor has it adequately considered the role of negative versus positive parenting simultaneously, thereby neglecting the potential overlap in both sets of constru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Their research focused on discerning the discrete impacts of negative and positive parenting on depressive and anxious symptoms through cognitive factors. The results of their study indicated that, when analysed in conjunction, greater negative parenting was directly associated with elevated levels of both depressive and anxious symptoms, whereas reduced positive parenting displayed distinct effects [13]. The relationship between less positive parenting and depressive symptoms was found to be mediated by negative self-concept and maladaptive attributional style, while the link between less positive parenting and anxious symptoms was mediated by positive selfconcept.…”
Section: The Impact Of Parenting Style and Relevant Factor On Adolesc...mentioning
confidence: 98%
See 1 more Smart Citation
“…Their research focused on discerning the discrete impacts of negative and positive parenting on depressive and anxious symptoms through cognitive factors. The results of their study indicated that, when analysed in conjunction, greater negative parenting was directly associated with elevated levels of both depressive and anxious symptoms, whereas reduced positive parenting displayed distinct effects [13]. The relationship between less positive parenting and depressive symptoms was found to be mediated by negative self-concept and maladaptive attributional style, while the link between less positive parenting and anxious symptoms was mediated by positive selfconcept.…”
Section: The Impact Of Parenting Style and Relevant Factor On Adolesc...mentioning
confidence: 98%
“…Meanwhile, Rodriguez and colleagues investigated the interplay between parental behaviour, cognitive variables encompassing negative self-concept and maladaptive attributional styles, and internalizing issues involving symptoms of depression and anxiety among a sample of children aged 7 to 11. In the context of primary school-age children, it was observed that maladaptive attributional styles and negative selfconcepts demonstrated a moderate level of correlation [13]. Self-concept refers to the way an individual perceives themselves, and their beliefs about their own abilities, qualities, and characteristics.…”
Section: The Impact Of Parenting Style and Relevant Factor On Adolesc...mentioning
confidence: 99%
“…It is defined as the upbringing of children by their parents, who also take responsibility for their emotional, social, intellectual, and physical development (Phillips et al ., 2017;Massar & Patil, 2019) . For many years, researchers have been interested in the issues related to parental practices, which have been described using different terminology, such as parenting (Rodriguez et al ., 2022), parenting styles (Baumrind, 1971;Hou et al ., 2020), parental attitudes and dimensions (Reid et al ., 2015), or parental practices (Smokowski et al ., 2015) . Most measures intended to assess parental behaviour are based on the theoretical concept of the parenting style typology created by Diana Baumrind (1971) .…”
Section: Introduction Parental Attitudesmentioning
confidence: 99%